2011
DOI: 10.4207/pa.2011.art42
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Rhino Cave, located at the World Heritage site of Tsodilo Hills, is one of the three main Middle Stone Age (MSA) sites in Botswana. Initial investigations during the mid-1990s left unanswered a number of key questions regarding the early use of the cave. This prompted the current investigations, which have unearthed a wealth of MSA artifacts from a lag deposit. Results of a selectively employed chaîne opératoire analysis have revealed a very special set of behavioral patterns. It will be argued that the best-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 107 publications
(148 reference statements)
0
12
0
Order By: Relevance
“…A recent genetic analysis has confirmed that El Castillo was more likely created by Cro-Magnons than Neanderthals (Wood et al, 2014), which suggests that this form of costly ritual behavior was part of the Homo sapiens' repertoire prior to their exodus from Africa, and indeed recent evidence confirms this. At Rhino Cave in Botswana (Southern Africa), evidence has been found for some of the earliest cave rituals, dating as far back as 70,000 ybp (Coulson, Staurset, & Walker, 2011). 2011to argue that it was a likely assembly site for hominin communities in the region.…”
Section: Cavesmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent genetic analysis has confirmed that El Castillo was more likely created by Cro-Magnons than Neanderthals (Wood et al, 2014), which suggests that this form of costly ritual behavior was part of the Homo sapiens' repertoire prior to their exodus from Africa, and indeed recent evidence confirms this. At Rhino Cave in Botswana (Southern Africa), evidence has been found for some of the earliest cave rituals, dating as far back as 70,000 ybp (Coulson, Staurset, & Walker, 2011). 2011to argue that it was a likely assembly site for hominin communities in the region.…”
Section: Cavesmentioning
confidence: 99%
“…There are also an unusually large number of burned and broken tools in the cave produced from colorful, nonlocal raw materials ("exotic" tools). These raw materials were transported to the cave from distances ranging from 50 to several hundred kilometers (Coulson et al, 2011). At the cave, the raw materials were fashioned into tools (points) and then intentionally destroyed and burned.…”
Section: Cavesmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, further depictions of animals in profile, including a possible zebra and rhinoceros, have been identified from the same series of Apollo 11 Cave plaquettes on which the therianthropic-like figure was identified (Rifkin, Henshilwood, and Haaland, forthcoming). Moreover, a large natural stone outcrop in Rhino Cave (Tsodilo Hills, Botswana, Africa), dating to the Middle Stone Age seems to have been regarded as a snake as it was embellished with multiple pock marks (Coulson, Staurset, and Walker 2011). As relatively complex tools and evidence for 'art' -though not representational depiction (but see Hodgson 2013a) -are increasingly coming to light from southern Africa dating up to and, in some cases, more than 100,000 BP (Lombard 2006(Lombard , 2011Marean 2010;Henshilwood, d'Errico, and Watts 2009), Klein's (2000) and others' contention that a genetic mutation 50 ka led to the proliferation of ornaments, sculpture, animal depictions etc., in Europe during the Upper Palaeolithic is seriously challenged.…”
Section: Introductionmentioning
confidence: 99%
“…Since prehistoric times, death and aging have been of great interest to humanity [3][4][5][6]. This concern about death is not unique to humans, it also exists in some of the higher mammal species [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%